A high-performance asymmetric supercapacitor based on Ni3S2-coated NiSe arrays as positive electrode. (18th January 2019) - Ye, Beirong; Gong, Chao; Huang, Miaoliang; Ge, Jinhua; Fan, Leqing; Lin, Jianming; Wu, Jihuai
Abstract : Cotton-like Ni3 S2 -coated NiSe rod composite electrode was synthesized by cyclic voltammetry electrodeposition with satisfactory electrochemical performance. Abstract : NiSe rods coated with cotton-like Ni3 S2 were directly grown on nickel foam through a two-step process, comprising selenization and electrodeposition. The as-obtained NiSe/Ni3 S2 composite electrode exhibited excellent electrochemical properties, with a high specific capacitance of 8.81 F cm −2 (1259.3 F g −1 ) at a current density of 4 mA cm −2, which was better than the value of pure NiSe electrode (5.17 F cm −2 ; 861.8 F g −1 ) at the same current density. Moreover, an asymmetric supercapacitor (ASC) was fabricated using NiSe/Ni3 S2 electrode and AC electrode as positive electrode and negative electrode, respectively. This ASC extended the potential window to 1.6 V and was possessed of a superior energy density of 38.7 W h kg −1 at a power density of 192 W kg −1, with outstanding cycling stability (85.9% retention after 10 000 cycles).